Penerapan Data Mining Untuk Prediksi Penjualan Produk Terlaris Menggunakan Metode K-Nearest Neighbor - Dewi, Sri Puspita; Nurwati, Nurwati; Rahayu, Elly (Forum Kerjasama Pendidikan Tinggi, 2022)
The implementation of Data Mining is very much needed by UD Andar because this trading business sells various types of products. This trading business sells powdered herbal medicine, plastic bags, food & beverage ingredients, and frozen foods that are in demand by consumers. Judging from the large number of consumer requests, it turns out that there are several best-selling and not-selling products, so based on the last 1 year data, a prediction of the best-selling product sales is needed, in order to make it easier for trading businesses in planning stock providers. Because the current system is still manual, the data obtained is less accurate and efficient. So to overcome this, we need a sales prediction system for best-selling products with data mining techniques using the k nearest neighbor method. This research produces a system of k nearest neighbor algorithms in data mining techniques that help to predict the sales of the best-selling products at UD Andar